Heat transfer characteristics of MHD flow of Williamson nanofluid over an exponential permeable stretching curved surface with variable thermal conductivity. (December 2021) - Ahmed, Kamran; Akbar, Tanvir; Muhammad, Taseer; Alghamdi, Metib
Abstract: This study aims to investigate the flow of two-dimensional magnetohydrodynamics (MHD) Williamson nanofluid over the permeable exponential stretching curved surface with variable thermal conductivity and activation energy. The Navier Stokes Equation along with Williamson fluid model is used to govern the partial differential equations (PDEs) and to transfer these PDEs into ordinary differential equations (ODEs), appropriate similarity transformations are utilized. The obtained ODEs are solved numerically. The effect of the physical parameters that are Williamson fluid parameter, curvature parameter, permeability parameter, temperature factors (Biot, Brinkman, thermal conductivity, temperature ratio, temperature difference, radiation, unequal heat source/sink), suction/injection parameter, magnetic parameter, nanofluid parameters (Brownian motion, thermophoresis), activation energy factors (reaction rate, fitted rate constant), Schmidt number, on velocity, pressure, temperature, and concentration profiles are shown through graphs.